Logistical factors associated with adverse outcomes following emergency surgery in an acute care surgical unit - Nel, Daniel Benjamin (Division of General Surgery, 2022)
Purpose The Acute Care Surgical Unit at Groote Schuur Hospital was established in 2010 and is the first of its kind in Africa. The aim of this study was to describe the outcomes of emergency surgical cases, as well as determine the logistical factors associated with adverse outcomes following surgery within the unit. Methods This study was a retrospective audit which reviewed the folders of adult patients who underwent an emergency surgical procedure from July 2016 to July 2017. The primary outcome was a major adverse event (AE) which was defined by a Clavien-Dindo score of 3-5. A number of logistical factors related to patient admission and operation were evaluated for association with outcomes. Results A total of 271 patients were included with an mean age of 47 years, with 48% females and 52% males. A major AE was recorded for 13% of patients. The following factors were found to be predictive of a major AE: referral from outside the hospital, urgent booking colour code, reoperation and consultant most senior surgeon present during procedure. Patient admission/surgery performed outside of normal working hours, being booked for surgery on admission, as well as delay to surgery beyond colour code were not associated with a major AE. Conclusion Apart from traditional clinical parameters, factors related to perioperative logistics may contribute to the risk of a major AE after emergency surgery and should be considered for inclusion in more comprehensive predictive models for adverse outcomes within an acute care surgery unit.